Impairment of Endothelial Cell Function Induced by Hemoglobin A1c and the Potential Mechanisms - Bo, J.; Guan, Y.; Guo, Y.; Xie, S.; Zhang, C.; Zhang, H.; Chen, Z.; Lu, J.; Meng, Q. H. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Objective: Hemoglobin A1c (HbA1c) concentrations reflect glycemic control and diabetic complications. However, there is little evidence supporting the pathological role of HbA1c in the development and progression of diabetic complications. We investigated the impact of HbA1c on endothelial cell function and the potential mechanisms.Methods: The effects of HbA1c on the viability and migration of human umbilical vein endothelial cells (HUVECs) were measured by the Cell Counting Kit-8 and a wound healing scratch assay, respectively. Production of nitric oxide (NO) and reactive oxygen species was measured by the nitrate reductase colorimetric method and flow cytometry, respectively. The expression of endothelial nitric oxide synthase (eNOS) mRNA was quantitated by reverse-transcriptase PCR. The expression of eNOS, p-AMPK, and NOX4 proteins was detected by Western blot.Results: High concentrations of HbA1c reduced the viability and migration of HUVECs in a dose- and time-dependent manner. High concentrations of HbA1c inhibited production of NO but increased production of ROS. Incubation with increasing concentrations of HbA1c downregulated the expression of eNOS mRNA, decreased expression of eNOS and p-AMPK, and upregulated expression of NOX4.Conclusion: These findings provide direct evidence that HbA1c is involved in the development and progression of the cardiovascular complications of diabetes.
Keywords: diabetes mellitus; hemoglobin A1c; HUVECs; nitric oxide; reaction oxygen species; signal pathway